Social Media Marketing Strategy for MSME Adhiya Fashion - Eka Wanda Choirunnisa; Ikhwan Kholid (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This research aims to analyze the marketing strategies implemented by the MSME Adhiya Fashion to enhance competitiveness and expand market reach through social media. The study focuses on the application of the marketing mix (4P), consisting of Product, Price, Place, and Promotion. A descriptive qualitative approach was used, with data collected through observation, interviews, documentation, and questionnaires. The results indicate that social media platforms such as Instagram serve as the primary channel for Adhiya Fashion to showcase Products, engage with customers, and build brand awareness. Product strategies involving various hijab designs and appealing visual content have proven effective in attracting the attention of young consumers. Pricing strategies are adjusted to match the purchasing power of the target market, while distribution is carried out through online ordering systems. Promotional efforts include interactive content, special discounts, and the use of Digital trends. Despite the effectiveness of social media strategies, limitations in audience targeting and the minimal use of paid advertising features remain challenges. This research concludes that the integration of Digital marketing strategies based on the 4P framework can significantly contribute to the growth of MSMEs in the modest fashion sector.